Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41377-021-00642-2
|View full text |Cite
|
Sign up to set email alerts
|

Dirac-like cone-based electromagnetic zero-index metamaterials

Abstract: Metamaterials with a Dirac-like cone dispersion at the center of the Brillouin zone behave like an isotropic and impedance-matched zero refractive index material at the Dirac-point frequency. Such metamaterials can be realized in the form of either bulk metamaterials with efficient coupling to free-space light or on-chip metamaterials that are efficiently coupled to integrated photonic circuits. These materials enable the interactions of a spatially uniform electromagnetic mode with matter over a large area in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 111 publications
0
30
0
Order By: Relevance
“…J‐aggregates have been used in photonic structures, for example, to present strong coupling with inorganic multilayers [ 23 ] and to create all‐polymer photonic cavities. [ 24 ] Interestingly, the optical properties of films resulting from embedding TDBC into PVA can be modified as a function of the J‐aggregate concentration on the final films [ 7 ] obtaining films whose permittivity can reach ENZ values which correspond to a real part of the refractive index close to zero (below 0.5) in a bandwidth of tens of nanometers, [ 7,12 ] hence making them suitable as NZI materials. These NZI optical properties are obtained in the case of highly doped films with very large oscillator strengths, as high as f = 0.4, which provides a strong dispersive material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…J‐aggregates have been used in photonic structures, for example, to present strong coupling with inorganic multilayers [ 23 ] and to create all‐polymer photonic cavities. [ 24 ] Interestingly, the optical properties of films resulting from embedding TDBC into PVA can be modified as a function of the J‐aggregate concentration on the final films [ 7 ] obtaining films whose permittivity can reach ENZ values which correspond to a real part of the refractive index close to zero (below 0.5) in a bandwidth of tens of nanometers, [ 7,12 ] hence making them suitable as NZI materials. These NZI optical properties are obtained in the case of highly doped films with very large oscillator strengths, as high as f = 0.4, which provides a strong dispersive material.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the refractive index properties shown by thin films of J‐aggregates embedded in polymeric matrices can approach values suitable for near‐zero index materials (NZI). [ 8–12 ]…”
Section: Introductionmentioning
confidence: 99%
“…For on-chip applications, the PhCs with a Dirac-like cone would suffer from large radiative losses in the out-of-plane direction, because the Dirac-cone dispersion resides above the light line and the transverse dipole mode forming the Dirac-like cone can couple to extended plane waves in free space [30,31]. This would turn the PhC to be non-Hermitian, and hence the Diraclike cone would disappear, hindering its applications as the ultralow-loss ZIM.…”
Section: On-chip Applications With Cladding and Bic Techniquesmentioning
confidence: 99%
“…Besides the structural symmetry, Dirac cones can also be created by accidental degeneracy through engineering the material and geometrical parameters [29][30][31]. In 2011, Huang et al demonstrated a Dirac cone at the center of the Brillouin zone, i.e., the Γ point with k 0, of a square lattice of 2D dielectric PhC [32].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the so-called epsilon-near-zero (ENZ) materials, with a spectral region where the real part of the permittivity crosses zero, have emerged as one of the most promising platforms for all-optical switching. Naturally occurring homogeneous ENZ material comprises metals [1][2][3][4] and semiconductors [5][6][7], and ENZ regions may also be engineered with metamaterials [8][9][10][11][12][13][14][15][16]. They have been shown to exhibit exotic behaviors such as photon tunneling [10,[16][17][18], highly directional radiation [19][20][21], cloaking [22], and perfect absorption [23][24][25].…”
Section: Introductionmentioning
confidence: 99%